Incomplete development of second sacral lamina: a case report - Chauhan, Renu; Khanna, Jugesh (International Journal of Research in Medical Sciences, 2017)
Sacrum is made up of large fused 5 sacral vertebra forming posterior wall of pelvis. On routine examination of the bones present in the bone bank of our department we noticed a sacrum in which sacral canal was incompletely formed due to imperfect formation of second sacral laminae. Knowledge of such type of variation may be of importance to the clinicians in dealing with patients presenting with bladder and or bowel disturbances or presenting with some neurological deficit of the lower limb. Orthopaedic surgeons should also be aware of this anomaly while operating in the sacral region.